Autonomy or integration? Small-state responses to a changing European security landscape. Issue 3 (27th May 2017) - Haugevik, Kristin; Rieker, Pernille
ABSTRACT: In this special issue, we examine whether there is a pattern in how small European states, inside and outside of the European Union (EU), adapt and adjust to EU foreign and security policy. We assess selected European small states' room for manoeuvre within these fields, and within EU institutional structures more broadly, as part of everyday diplomatic interactions in Brussels and in the context of the rotating EU presidency. As the European integration process enters a new phase, possibly marked by a trend of more differentiated integration and flexibility of individual attachments, small states will continue to face the choice between formal autonomy and integration, and between de facto hesitance and adaptability. With Brexit, the remaining large states may become more influential, but small states will collectively have a majority of the votes and total population. Perhaps the coming era of European integration will become the era of small states.